Global left ventricular function assessment by ECG-gated multi-detector CT (MDCT): revised role in relation to 2D transthoracic echocardiography - Mohammed Elsayed Abdel Samea (The Egyptian Journal of Radiology and Nuclear Medicine, 2020)
Abstract Background An accurate and reproducible way for determining the left ventricular function is crucial to provide diagnostic and prognostic aspects of the pump activity of the heart. The MDCT of the heart can be that modality. We compared the 128 MDCT of fifty patients with their 2D echocardiography performed on the same day. Results Mean EF, ESV, EDV, and LV mass were 61.22 ± 9.50%, 70.23 ± 38.35, 172.22 ± 53.57, 164.63 ± 52.57 respectively on MDCT, and 61.14 ± 10.90%, 72.13 ± 32.69, 173.76 ± 62.45, 198.32 ± 72.54 respectively on echocardiography with moderate correlation in EF and good correlation in ventricular volumes (p < 0.05) using linear regression analysis. A Bland-Altman analysis showed that MDCT had slightly lower LFEF, LVESV, and LVEDV values with mean value of differences of 0.8, 2.4, and 2.28 respectively. Conclusion It is reasonable to use MDCT alone to assess LV function in patients already underwent coronary CT angiography.